Despite the hair failing, nails thrive… - Samipa Samir Mukherjee; B S Chandrashekar (Indian Journal of Paediatric Dermatology, 2017)
Ectodermal dysplasias are defined as a group of congenital, nonprogressive, developmental syndromes with primary disorders in at least two ectoderm-derived structures namely eccrine glands, hair, nail and teeth. Pure hair and nail affecting ectodemal dysplasias are exceedingly rare in occurance and have been known to be associated with multiple abnormalities, such as keratoderma or ichthyosis, skeletal and hematological abnormalities, cardiac irregularities, mental or psychomotor retardation and cataracts. We herein report a case of hypotrichosis with trichorrhexis nodosa and twenty nail dystrophy- a hypohidrotic ectodermal dysplasia variant.